The Influence Of Health Services On Personal Development Of Youth With disabilities In Elgeyo-Marakwet County, Kenya - Kurumei, William; Ogogo, Collin O.; KO’chung, Edward; Kimani, Cecilia (International Journal of Current Research, 2021)
Disability is a natural part of the human experience and therefore should not affect the rights of individuals to live independently, contribute to society, enjoy full inclusion in education and pursue a meaningful career. However, Youth with Disabilities (YWDs) in Elgeyo-Marakwet County, Kenya face socio-economic discrimination communally. Exclusion, isolation, abuse and lack of educational opportunities exist in Elgeyo-Marakwet County, Kenya. They do not enjoy the same human rights or equal access to goods and services as their peers without disabilities. The main objective of this study was to assess the influence of the socio-cultural support services on personal development of Youth with Disabilities in Elgeyo-Marakwet County Kenya. The specific objectives included determining the assistive technologies available for youth with disabilities in school in Elgeyo-Marakwet County. In addition, the study determined the influence of socio-cultural support services; education and vocational training, health services, employment and community perception on personal development (PD) of Youth with Disabilities in Elgeyo-Marakwet County. Two theories, Catherine Sanderson’s (2010) theory of socio-cultural perspective and Adams Stacy (1965) equity theory were studied to enable an understanding of the influence of the socio-cultural support services on personal development of Youth with Disabilities. A mixed methodology, using triangulation design with both quantitative and qualitative research was employed in this study to realize the objectives. The study targeted a total population of 492 of youth with disabilities, 320 parents of Youth with Disabilities in and out of school and 19 government officers. Sample size determination formula by Krejcie and Morgan (1970) was used to obtain the required sample of the Youth with Disabilities and their parents. Simple random sampling was used to select Youth with Disabilities and parents while purposive sampling was used to select government officers (key informants). A sample of 289 Youth with Disabilities, 175 parents and 19 government officers were picked for the study. Data was collected using questionnaires, interview schedule and an observation checklist. To determine content validity of the instruments, the supervisors were presented with the research instruments prior to the actual study. Their comments were adopted in modifying the instruments. The reliability of the instruments was established through a pilot study where a coefficient of Cronbach’s Alpha was determined, which was 0.741. Quantitative data were analyzed using descriptive statistics, while qualitative data were analysed thematically as the themes emerged. Study findings indicated that there was inadequate provision of socio-cultural support services which included education and vocational training, health services and employment. However, health services contributed 9.5%, to personal development of Youth with Disabilities. The study recommended, among others, funding of youth with disabilities support groups, initiating follow up support programs for youth with disabilities and wholly focusing on services that ensure that the ‘best’ is offered to the youth with disabilities as per government’s policies.The findings of this study may help in improving the education policy to have a focus on transition plans for youth with disabilities after school
Keywords: Disability is Universal; Isolation; Mistreatment.